Case report on a swift shift in uropathogens from Shigella flexneri to Escherichia coli: a thin line between bacterial persistence and reinfection - Kukwah Anthony Tufon; Djike Puepi Yolande Fokam; Youmbi Sylvain Kouanou; Henry Dilonga Meriki (BMC, 2020)
Abstract Background Urinary tract infections (UTI) are mostly caused by bacteria. Urine cultures are usually a definitive measure to select the appropriate antibiotics for the elimination of a uropathogen and subsequent recovery from the infection. However, the preferred antibiotics as determined by urine culture and sensitivity may still not eliminate the infection and would require further examination to ascertain the cause of treatment failure which could be unresolved bacteriuria, bacterial persistence, immediate reinfection with a different uropathogen or misdiagnosis. Case presentation A 2-years 7 months-old female was admitted in the Regional hospital of Buea following persistent fever. An auto medication with amoxicillin was reported. Urinalysis was done on the first day and the sediment of the cloudy urine revealed many bacteria and few pus cells. Ceftriaxone was prescribed as empirical treatment and a request for urine and blood culture was made. Three days after admission, the temperature and CRP were 39.0 °C and 96 mg/l, respectively. The urine culture results (> 105 CFU/ml of Shigella flexneri sensitive to ofloxacin) were presented to the doctor on the 4th day of admission. Patient was put on ofloxacin. Three days after, the temperature (38.5 °C) and CRP (24 mg/l) were still elevated. The blood culture result came out negative. A second urine culture was requested which came back positive (> 105 CFU/ml of Escherichia coli resistant to ofloxacin and sensitive to meropenem and amikacin). Ofloxacin was discontinued and the patient put on meropenem and amikacin. The third urine culture recorded no significant growth after 48 h of incubation. The patient was discharged looking healthy once more with a normal body temperature. Conclusion Antibiotics tailored towards the elimination of a particular bacterial species may as well provide a favorable environment for other bacterial species that are resistant to it in the course of treating a UTI episode. This apparent treatment failure may first of all require a second urine culture for confirmation rather than considering the possibilities of a misdiagnosis.